Concluding IGCP 503: Towards a holistic view of Ordovician and Silurian earth systems - Harper, David A.T.; Li, Jun; Munnecke, Axel; Owen, Alan W.; Servais, Thomas; Sheehan, Peter M. (EPISODES, 2011)
IGCP 503 'Ordovician Palaeogeography and Palaeoclimaté was established in 2004 primarily to identify the main drivers, both biological and geological, of the Great Ordovician Biodiversification Event. From the outset of the project it was clear that this event was part of a larger-scale, long-term, multifaceted process that included the end Ordovician extinction and Silurian recovery, if not more. IGCP 503 thus developed a major network that included scientists whose interests spanned the entire Lower Palaeozoic and encompassed a range of disciplines from classical palaeontology and palaeoecology through isotope geochemistry to climate modellin
Keywords: Ordovician; palaeogeography; palaeoclimate; GOBE; great ordovician biodiversification event; IGCP; Silurian recovery; Ordovician event; lower palaeozoic